청소년의 생활양식 유형과 정신건강 및 학교적응과의 관계 - 윤은종; Eun Jong Yoon; 김희수; Hee Soo Kim (청소년복지연구, 2005)
The purpose of this study was to examine the relationship of among types of life-style, mental health and school-related adjustments in adolescents. For this purpose, the data were collected by questionnaire from 432 high school students living in Pyungtaek. Statistical methods for the data analysis were oneway ANOVA and stepwise Regression by SPSS. The major results of this study are as follows: First, in the relationship between types of life-style and mental health, the getting type and the avoidance type have a positive effect on mental health in adolescents. Second, in the relationship between types of life-style and school-related adjustments, the useful type and the ruling type have a positive effect in school-related adjustments. but the avoidance has a negative effect on school-related adjustments. Third, in the relationship between mental health and school-related adjustments, the higher level of mental health have a negative effect on the school-related adjustments. Fourth, in the relationship between types of life-style, mental health and their school-related adjustments of adolescents, they could easily adapt to the relationship with useful type and depression, ruling type, hostility. KCI Citation Count: 23